x 4 − ( a 2 − 5 a + 6 ) x 2 − ( a 2 − 3 a + 2 ) = 0
Find the sum of all integral values of constant a for which only real roots exist for the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
first let t = x 2 2 t 2 − ( a 2 − 5 a + 6 ) t − ( a 2 − 3 a + 2 ) = 0 by the quadratic formula, t = 2 a 2 − 5 a + 6 ± ( a 2 − 5 a + 6 ) 2 + 4 ( a 2 − 3 a + 2 ) hence x = 2 a 2 − 5 a + 6 ± ( a 2 − 5 a + 6 ) 2 + 4 ( a 2 − 3 a + 2 ) , − 2 a 2 − 5 a + 6 ± ( a 2 − 5 a + 6 ) 2 + 4 ( a 2 − 3 a + 2 ) for all x to be real , 2 a 2 − 5 a + 6 − ( a 2 − 5 a + 6 ) 2 + 4 ( a 2 − 3 a + 2 ) ≥ 0 now ,we get − ( a 2 − 5 a + 6 ) 2 + 4 ( a 2 − 3 a + 2 ) ≥ a 2 − 5 a + 6 ( a 2 − 5 a + 6 ) 2 + 4 ( a 2 − 3 a + 2 ) ≤ ( a 2 − 5 a + 6 ) 2 a 2 − 3 a + 2 ≤ 0 ( a − 1 ) ( a − 2 ) ≤ 0 1 ≤ a ≤ 2 hence, the sum of the integral values are 1 + 2 = 3
T h e g i v e n e q u a t i o n i s q u a d r a t i c i n x 2 . S o r e a l v a l u e s x 2 c a n n o t b e n e g a t i v e . ( a 2 − 5 a + 6 ) = ( a − 2 ) ( a − 3 ) , ( a 2 − 3 a + 2 ) = ( a − 2 ) ( a − 1 ) . S o t h e p r o d u c t o f r o o t s i s − ( a − 2 ) ( a − 1 ) , w h i c h i s n e g a t i v e o r 0 . S o o n l y p o s s i b l e s o l u t i o n i s i f x 2 = 0 . S o i f a = 2 , i t i s e a s y t o s e e x 4 = 0 . o n l y r o o t s a r e r e a l 0 s . I f a = 1 , x 4 − 2 x 2 − 0 = 0 , g i v e s x 2 = 0 o r x 2 = 2 . S o l u t i o n a r e 0 , 0 , − 2 , 2 r e a l r o o t s . S o a = 1 o r a = 2 a r e o n l y s o l u t i o n s . S o 1 + 2 = 3 .
Problem Loading...
Note Loading...
Set Loading...
The given equation x 4 − ( a − 3 ) ( a − 2 ) x 2 − ( a − 1 ) ( a − 2 ) = 0 → ( 1 )
can be written as: t 2 − ( a − 3 ) ( a − 2 ) t − ( a − 1 ) ( a − 2 ) = 0
where t = x 2
Now, the roots of this equation have to be positive or else the roots of ( 1 ) will be imaginary, thus
i ) The product of the roots − ( a − 1 ) ( a − 2 ) ≥ 0
i i ) The sum of the roots ( a − 3 ) ( a − 2 ) ≥ 0
From ( i ) we have 1 ≤ a ≤ 2
and from ( i i ) we have a ≤ 2 , 3 ≤ a
The overlapping interval is 1 ≤ a ≤ 2
Hence the sum of the integral values of a = 1 + 2 = 3